Challenges Faced by Nurses in Transitioning Pediatric Sickle Cell Disease Patients to Adult Care - Gifty Enyonam Amoaku; Delali Adwoa Wuaku; Vivian Efua Senoo-Dogbey (SAGE Open Nursing)
Background Sickle-cell disease is a common genetic red blood cell disorder with global concern. Sub-Saharan Africa, including Ghana, is most predominantly affected. Improvement in medicine has enhanced children's survival into adulthood; hence the need to transition them into adult care services. Well-transitioned patients manage the condition without undue disruptions in their quality of life. Aim To explore the challenges faced by nurses in transitioning pediatric patients to adult care. Method The study adopted a phenomenological descriptive qualitative design to describe and interpret the difficulties nurses encounter when providing transition care to adolescent patients. Purposive sampling and convenience sampling methods were used to select 15 professional nurses from the pediatric department. Thematic content analysis was used to analyze the data. The interview transcripts were read to identify emerging themes and sub-themes and exported into Nvivo 12 software. Results Nurses working at the pediatric department of the regional health facility had no education on how to transition children from pediatric to adult care, leading to poor evidence-based transition care. In addition, there was a lack of transitional care protocol, staff training, care collaboration, transition planning, follow-up initiatives to track and monitor progress, difficulty in tracking the transition process, increased workload, and transition resource constraints. Conclusion Nurses at the regional health facility have inadequate education on transitional care of adolescent patients, in-service training and workshop on transitional care on the management of patients, and formulating a policy on transitional care to guide nurses at the pediatric unit.